SELF COMPACTING CONCRETE USING FLY ASH AND DUST STONE AS FILLER MATERIAL - Patrisia, Yulin (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2014)
Self-compacting concrete is a concrete variant that has the ability to condense itself, because the workability and flowability of the high concrete. There are many advantages obtained when a construction using SCC. However, the limited knowledge of the SCC makes this concrete variant is less used in construction work. Through experimental research methods in the laboratory, by making the SCC mixture using 20% dust stone and fly ash variation of 0%, 10%, 20%, and 30%, obtained results (1) the addition of fly ash composition on the concrete made the flowability of concrete increased; (2) along with the addition of a maximum of 30% FA, the higher the viscosity of concrete, which is indicated by the smaller the value of T500; (3) along with the addition of FA, the value of the passing ability of SCC (blocking ratio value increases) increased; (4) The results testing of the compressive strength of concrete age of 7 and 28 days showed an increase due to the addition of FA of 0%, 10%, 20%, and 30% in SCC concrete mix.